Ecological Experiences And Perceptions Of Small-Scale Gillnet And Purse Seine Fishers On Seabirds And Other Non-Target Taxa In The Humboldt Current System, Chile - Suazo, Cristián G.; Anguita, Cristóbal; Ojeda Villarroel, Jaime Andrés; Luna-Jorquera, Guillermo; Sepúlveda, Maritza; Yates, Oliver (My University, 2024)
Strategies to reduce the negative impacts of fisheries on ecosystems often come into conflict with fishers who have different experiences with, and perceptions of, biodiversity compared to policy makers and fisheries managers. We interviewed 800 fishers along 2400 kilometers of the Humboldt Current System (HCS) coast, assessing fishers' perceptions of the impacts of marine predators on fishing and their proposals to reduce conflicts with small-scale net fisheries. Vessel captains saw seabirds as positive indicators of fish presence along the HCS (mean probability 62.7%). In contrast, sea lions were perceived negatively, affecting catches for all fishers and causing fishing gear damage among gillnet fishers (97.1%). Among different measures suggested by fishers to reduce conflicts with non-target taxa, night fishing and marine protected areas (MPAs) were viewed as least likely to be implemented because these affect fishing performance (6% and 13.1%) through changes to at-sea safety and fishing effort displacement, respectively. In contrast, economic compensation and culling of currently protected sea lions were the most popular but also the most sensitive measures (31% and 33%, respectively). Different dimensions of experiences and perceptions of fishers are key to the bottom-up understanding of interactions in small-scale fisheries. This is especially true when measures to mitigate their impacts do not have any consolidated installation/monitoring, which is a continuing challenge for these types of fisheries globally. This study emphasizes the role of small-scale fishers as a source of diverse ecological experiences and perceptions to complement knowledge on sensitive conservation issues.
Keywords: Artisanal Fisheries; Ecological Knowledge; Fisheries; Management; Mitigation; Multispecies